Hsa-miR-31 Governs T-Cell Homeostasis in HIV Protection via IFN-γ-Stat1-T-Bet Axis - Zhu, Lingyan; Qiu, Chao; Dai, Lili; Zhang, Linxia; Feng, Meiqi; Yang, Yu; Qiu, Chenli; Zhang, Anli; Huang, Jun; Wang, Ying; Wan, Ying; Zhao, Chen; et al. (Frontiers in Immunology, 2021)
It remains poorly defined whether any human miRNAs play protective roles during HIV infection. Here, focusing on a unique cohort of HIV-infected former blood donors, we identified miR-31 (hsa-miR-31) by comparative miRNA profiling as the only miRNA inversely correlating with disease progression. We further validated this association in two prospective cohort studies. Despite conservation during evolution, hsa-miR-31, unlike its mouse counterpart (mmu-miR-31), was downregulated in human T cell upon activation. Our ex vivo studies showed that inhibiting miR-31 in naïve CD4+ T cells promoted a transcriptional profile with activation signature. Consistent with this skewing effect, miR-31 inhibition led to remarkably increased susceptibility to HIV infection. The suppressive nature of miR-31 in CD4+ T cell activation was pinpointed to its ability to decrease T-bet, the key molecule governing IFN-γ production and activation of CD4+ T cells, by directly targeting the upstream STAT1 transcriptional factor for downregulation, thus blunting Th1 response. Our results firmly established miR-31 as a clinically useful biomarker for prediction of HIV disease progression and, by demonstrating its importance in tuning the activation of CD4+ T cells, implicated that miR-31 may play critical roles in other physiological contexts where the CD4+ T cell homeostasis needs to be deliberately controlled.